2011
DOI: 10.1186/1745-6215-12-197
|View full text |Cite
|
Sign up to set email alerts
|

Promoting smoking cessation in Pakistani and Bangladeshi men in the UK: pilot cluster randomised controlled trial of trained community outreach workers

Abstract: BackgroundSmoking prevalence is high among Pakistani and Bangladeshi men in the UK, but there are few tailored smoking cessation programmes for Pakistani and Bangladeshi communities. The aim of this study was to pilot a cluster randomised controlled trial comparing the effectiveness of Pakistani and Bangladeshi smoking cessation outreach workers with standard care to improve access to and the success of English smoking cessation services.MethodsA pilot cluster randomised controlled trial was conducted in Birmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Results from other smokeless tobacco trials have reported the value of NRT in reducing withdrawal symptoms and NRT-related adverse events during quit attempts [13][14][15][16][17][18][19]. Participant satisfaction with English NHS SSS has been reported previously to be high [23,33]. Oral pain was reported commonly by clients at the start of the quit attempt, as in a previous study [9].…”
Section: What Is Already Knownsupporting
confidence: 55%
See 2 more Smart Citations
“…Results from other smokeless tobacco trials have reported the value of NRT in reducing withdrawal symptoms and NRT-related adverse events during quit attempts [13][14][15][16][17][18][19]. Participant satisfaction with English NHS SSS has been reported previously to be high [23,33]. Oral pain was reported commonly by clients at the start of the quit attempt, as in a previous study [9].…”
Section: What Is Already Knownsupporting
confidence: 55%
“…A cessation trial with male smokers of South Asian (Pakistani, Bangladesh) origin has also indicated the benefits of providing a specialist outreach service for otherwise 'hard-to-reach' participants [23].…”
Section: What Is Already Knownmentioning
confidence: 99%
See 1 more Smart Citation
“…The main exception was in relation to smoke-stop services, where services to support quitting are viewed as cost-effective and approaches that provide ongoing support for smokers wanting to stop, or those who have quit, delivered in a targeted way, are more likely to be effective. 252,[439][440][441][442] In addition, there is still potential for better identification of smokers and raising smoking awareness by a range of health and other care professionals. The evidence to support interventions for increasing exercise or reducing weight was limited and suggested that such approaches in primary care or in schools have little impact and that any benefit is generally only short-term.…”
Section: Resultsmentioning
confidence: 99%
“…[248][249][250] However, few studies examined specific population groups although one study suggests a lack of services for ethnic minority groups despite some evidence of the benefit of community outreach services. 251,252 Identifying strategies to find and support smokers from disadvantaged groups is, therefore, of key importance. 253 This systematic review identified 48 papers.…”
Section: Smoking Cessationmentioning
confidence: 99%